Effect of Gd doping on the structural, luminescence and magnetic properties of ZnS nanoparticles synthesized by the hydrothermal method. (September 2016) - Poornaprakash, B.; Chalapathi, U.; Reddeppa, Maddaka; Park, Si-Hyun
Abstract: This paper reports the synthesis and characterization of ZnS:Gd nanoparticles prepared by a hydrothermal process using different doping concentrations. The chemical, structural, luminescence and magnetic properties of these nanoparticles were investigated by X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), photoluminescence (PL) spectroscopy, and vibrating sample magnetometer (VSM) measurements. XRD confirmed that all the samples had a cubic structure with good crystallinity. HRTEM showed that the particles were polycrystalline with a mean size of 4–6 nm. XPS revealed the oxidation state of Gd in the ZnS lattice to be +3. The PL spectra of all the nanoparticles exhibited broad emission peaks in the visible region. All the Gd doped nanoparticles exhibited well-defined ferromagnetic behavior at room temperature. The saturation magnetization increased significantly with increasing Gd concentration, reaching a maximum for 3 at.% Gd and decreasing for the 5 at.% Gd doped ZnS nanoparticles. Highlights: ZnS:Gd (0, 1, 3 and 5 at.%) nanoparticles were synthesized by a hydrothermal route. ZnS:Gd nanoparticles exhibited broad and asymmetric PL peaks in the visible region. Gd-doped ZnS nanoparticles exhibited well-defined room temperature ferromagnetism. This is the first report of the magnetic properties of ZnS:Gd in any form.